Psychobiological Mechanisms of Placebo and Nocebo Effects Pathways to Improve Treatments and Reduce Side Effects. [article]. - Petrie, Keith J.
Placebo effects constitute a major part of treatment success in medical interventions. The nocebo effect also has a major impact, as it accounts for a significant proportion of the reported side effects for many treatments. Historically, clinical trials have aimed to reduce placebo effects; however, currently, there is interest in optimizing placebo effects to improve existing treatments and in examining ways to minimize nocebo effects to improve clinical outcome. To achieve these aims, a better understanding of the psychological and neurobiological mechanisms of the placebo and nocebo response is required. This review discusses the impact of the placebo and nocebo response in health care. We also examine the mechanisms involved in the placebo and nocebo effects, including the central mechanism of expectations. Finally, we examine ways to enhance placebo effects and reduce the impact of the nocebo response in clinical practice and suggest areas for future research. -- (from the author)